2014
DOI: 10.1007/s11095-014-1573-2
|View full text |Cite
|
Sign up to set email alerts
|

Release, Partitioning, and Conjugation Stability of Doxorubicin in Polymer Micelles Determined by Mechanistic Modeling

Abstract: Purpose To better understand the mechanistic parameters that govern drug release from polymer micelles with acid-labile linkers. Methods A mathematical model was developed to describe drug release from block copolymer micelles composed of a poly(ethylene glycol) shell and a poly(aspartate) core, modified with drug binding linkers for pH-controlled release [hydrazide (HYD), aminobenzoate-hydrazide (ABZ), or glycine-hydrazide (GLY)]. Doxorubicin (Dox) was conjugated to the block copolymers through acid-labile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Solvato-fluorochromic methods measure drugs remaining in the nanoparticle core, while HPLC methods measure drugs inside the nanoparticle core and drugs outside the core, which may be bound to polymers or remain in the aqueous environment [45]. Drugs bound to polymers or in solution are not expected to affect in vivo drug release rates, even though they can significantly affect HPLC measurements [46]. Although mechanistic modeling has been used to correct for these interactions in HPLC methods, solvato-fluorochromic methods provide a unique opportunity to directly measure drug release from the nanoparticle core during drug release measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Solvato-fluorochromic methods measure drugs remaining in the nanoparticle core, while HPLC methods measure drugs inside the nanoparticle core and drugs outside the core, which may be bound to polymers or remain in the aqueous environment [45]. Drugs bound to polymers or in solution are not expected to affect in vivo drug release rates, even though they can significantly affect HPLC measurements [46]. Although mechanistic modeling has been used to correct for these interactions in HPLC methods, solvato-fluorochromic methods provide a unique opportunity to directly measure drug release from the nanoparticle core during drug release measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional pharmacokinetics and pharmacodynamics (PK/PD) correlate efficacy of small molecule drugs with time-dependent changes in average bulk drug concentration at the site of action. However, it has been shown that these PK/PD methods often fail to predict efficacy of drug-loaded NV that control drug concentrations in vascular, interstitial and intracellular spaces of tumor ( Ponta and Bae, 2014 ; Ponta et al, 2015 ; Curtis et al, 2016b ). In addition, traditional analyses frequently simplify or rule out tumor physiology changing over time ( Khawar et al, 2015 ; Khalid et al, 2016 ).…”
Section: Modeling Of Cancer Nanotherapy Taking Into Account the Micromentioning
confidence: 99%
“…In the empirical model above, the variables , , and , refer to the control factors of reservoir pH (7.0, 7.4, and 7.8), reservoir concentration of total ammonia (0, 50, and 100 mM), and the dilution factor of the liposomal suspension in the dialysis tube (8,16, and 24-fold), respectively. Regression was performed using Minitab v 16.1 software for all the constants (a i , b i , and c i ) in Eq.…”
Section: Empirical Dxr Release Modelmentioning
confidence: 99%
“…[11,15,16,19] Drug transport kinetics across the dialysis membrane are likely to vary with the drug of interest in the study, either by having an increased or decreased rate of transport across the membrane, or because of processes associated with the equilibria and kinetics of drug binding to the dialysis membrane. The present study considered a mechanism in line with the latter scenario to describe DXR dialysis membrane transport.…”
Section: Comparison Of Dialysis Transport Models For Evaluating Liposmentioning
confidence: 99%